New insights into smoking and urinary tract infections during pregnancy using pregnancy-pair design: A population-based register study - Wallin Hanna P; Gissler Mika; Korhonen Päivi E; Ekblad Mikael O (WILEY, 2022)
Introduction: Pregnancy itself predisposes to urinary tract infections (UTI). There appears to be a higher prevalence of infections and genitourinary diseases among pregnant smokers than among non-smokers. The present study is a retrospective observational register study aiming to investigate whether maternal smoking is associated with the prevalence of UTIs during pregnancy by utilizing a pregnancy-pair analysis.
Material and methods: Information about pregnancies and maternal smoking was obtained from the Finnish Medical Birth Register. The study sample consisted of all singleton pregnancies (n = 723 433) of women giving birth between January 2006 and December 2018 in Finland. Information on maternal smoking was collected in three categories: (1) non-smoking; (2) quit smoking during the first trimester; and (3) continued smoking throughout the pregnancy. Information about maternal UTI diagnoses during pregnancy was received from the Hospital Discharge Register and the Medical Birth Register. UTIs were categorized as lower and upper UTIs according to the International Statistical Classification of Diseases and Related Health Problems (ICD)-10 diagnosis codes. Risks were calculated as odds ratios (OR) by logistic regression with 95% confidence intervals (CI) further adjusted for maternal characteristics (aOR). Finally, pregnancy-pair analyses were performed: mothers who had changed smoking status (no smoking/any smoking) between consecutive pregnancies (n = 27 246 pregnancy-pairs) were analyzed as one cluster and compared with non-smokers.
Results: Smokers had UTIs more often compared with the non-smokers. The association was even stronger among those who continued to smoke (aOR 1.60, 95% CI 1.51-1.70) than among those who smoked only during the first trimester (aOR 1.27, 95% CI 1.18-1.37) compared with non-smokers. In pregnancy-pair analysis, smoking was associated with upper UTIs during pregnancy (OR 1.49, 95% CI 1.05-2.12) compared with non-smokers, but after the adjustments this association was attenuated (aOR 1.27, 95% CI 0.88-1.82). No association in lower UTIs was observed in the pregnancy-pair design.
Conclusions: Maternal smoking was associated with a higher prevalence of UTIs during pregnancy in the standard comparison. The observed association was fully attenuated in the pregnancy-pair analysis, in which smoking was dichotomized. This study suggests that the association between maternal smoking during pregnancy and adverse maternal health effects might be more complex than previously thought.